Isolasi Bakteri Asam Laktat Berpotensi Probiotik Pada Dangke, Makanan Tradisional dari Susu Kerbau di Curio Kabupaten Enrekang - Nur, Fatmawati; H, Hafsan; Wahdiniar, Andi (Jurusan Biologi UIN Alauddin Makassar, 2015)
This research is a preliminary study to explore potential probiotics of Lactic Acid Bacteria (LAB) in dangke, a traditional food from buffalo milk in Curio the district of Enrekang. Isolation of LAB performed using the selective medium de Man Rogosa Sharpe Agar. LAB will show clear zone on MRS medium after the addition of the indicator in the form of CaCO3 and incubated for 24 hours. Selection is done by observing the cell morphology and Gram staining. Further testing with the biochemical properties of sugar fermentation test. The results showed that lactic acid bacteria isolates obtained consists of two species of Lactobacillus plantarum and Lactobacillus fermentum.Keywords: Buffalo milk, dangke, Lactic Acid Bacteria, probiotic